The effectiveness of ground‐based applications of Bacillus thuringiensis var. kurstaki for controlling oak processionary moth Thaumetopoea processionea (Lepidoptera: Thaumetopoeidae). (24th January 2022) - Straw, Nigel A.; Forster, Jack
Abstract: The effectiveness of ground‐based applications of Bacillus thuringiensis var. kurstaki ( Btk ) for controlling oak processionary moth (OPM) was evaluated by comparing the numbers of larval nests on treated and untreated oak trees in Richmond Park, in west London, UK. A total of 760 oak trees ( Quercus robur ) were monitored over a period of 4 years from 2014 to 2017, and the effects of current treatment and previous treatment history on nest numbers were analysed using general linear mixed models. Two applications of Btk applied 7–10 days apart in the spring, just after egg hatch, reduced the numbers of larval nests by 86–94%. In 2015, the effectiveness of treatment decreased as tree height increased, whereas in 2016 and 2017 nest numbers were reduced by a similar percentage across all tree height classes. The effects of treatment were relatively short‐lived, because at the scale at which the insecticide applications were carried out, trees were re‐colonised rapidly by adult OPM flying in from the surrounding area. Consequently, nest numbers generally returned to pre‐treatment densities within 1–2 years. Abstract : This paper describes the results of a four‐year study investigating the effectiveness of ground‐based applications of the biological insecticide Bacillus thuringiensis for controlling oak processionary moth (OPM). Larvae of the moth construct silken nests on oak trees and treatment with B. thuringiensis reduced the numbers of nests by 86‐94%. In 2014, 2016 and 2017, the insecticide treatments were equally effective across all tree height classes, whereas in 2015 treatment was less effective on trees that were more than 25 m tall.